2016
DOI: 10.1016/j.cmi.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Tools for opening new chapters in the book of Treponema pallidum evolutionary history

Abstract: Treponema pallidum infections causing yaws disease and venereal syphilis are globally widespread in human populations, infecting hundreds of thousands and millions annually respectively; endemic syphilis is much less common, and pinta has not been observed in decades. We discuss controversy surrounding the origin, evolution and history of these pathogens in light of available molecular and anthropological evidence. These bacteria (or close relatives) seem to affect many wild African nonhuman primate (NHP) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 41 publications
(59 reference statements)
1
39
0
3
Order By: Relevance
“…We previously described Bcbva diversity within carcasses and found that isolates Treponemal DNA DNA extracts were tested using a PCR amplifying a 67-bp DNA fragment, including primers from the DNA polA gene (described in Leslie, Azzato, Karapanagiotidis, Leydon, & Fyfe, 2007). An additional PCR using fusion primers was performed to append M13F/R sequences to first-round amplicons and thereby enable their sequencing (as described in Gogarten et al, 2016). We tested the sensitivity of this assay and found it was able to detect as few as 10 template molecules spiked into fly extracts (see Appendix S1 for details).…”
Section: Pathogen Screeningmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously described Bcbva diversity within carcasses and found that isolates Treponemal DNA DNA extracts were tested using a PCR amplifying a 67-bp DNA fragment, including primers from the DNA polA gene (described in Leslie, Azzato, Karapanagiotidis, Leydon, & Fyfe, 2007). An additional PCR using fusion primers was performed to append M13F/R sequences to first-round amplicons and thereby enable their sequencing (as described in Gogarten et al, 2016). We tested the sensitivity of this assay and found it was able to detect as few as 10 template molecules spiked into fly extracts (see Appendix S1 for details).…”
Section: Pathogen Screeningmentioning
confidence: 99%
“…NHPs in TNP are also infected with TPE and present with severe lesions (Figure a; Gogarten et al, ; Knauf et al, ). Many mangabeys in the study group (referred to as the Audrenisrou group) presented with symptoms of yaws during the study period (16% of individuals; data not shown) and full TPE genomes generated from lesion samples confirmed this pathogen is present in animals collected in the study group with these symptoms (Knauf et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may not yet have been identified because they exhibit few indicative diagnostic characteristics through culture morphology (Kom arek et al 2014;Sciuto and Moro 2015), attenuated growth capacity or unclear growth requirements in culture, making them difficult to identify by traditional methodology (Youssef et al 2014;Sciuto and Moro 2015). In addition, they may not be able to be cultivated, thus known as viable, but not cultivable, which is either a transitory state for some bacteria in response to the environment stress, such as the Vibrio genus (Griffitt et al, 2011;Zhong et al 2016;Chahorm and Prakitchaiwattana 2018) or a stable state, as occurs in Mycobacterium leprae and Treponema pallidum (Petricha et al 2015;Ruiz-Fuentesa et al 2015;Gogarten et al 2016;Steinmann et al 2017). Thus, in both cases, applying molecular biology tools allows for their taxonomic classification, for the evaluation of their pathogenic potential and serve as a diagnostic method (Bergholz et al 2014;Das et al 2014;Kergourlay et al 2015;Sciuto and Moro 2015;King et al 2017).…”
Section: Introductionmentioning
confidence: 99%